Perancangan Aplikasi Registrasi Kegiatan Berbasis Web Menggunakan Framework CodeIgniter di Fakultas Teknologi Informasi - Jonathan Febrianto Gunawan; Ramos Somya (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Activities are part of students’ activities that are often carried out in the campus environment, both mandatory and non-mandatory activities. Mandatory activities have become the main activities every year, such as Student activities carried out in each faculty. The problem that occurs at this time is that there is no application to help carry out activities at the faculty so that errors often occur in data management in the Registration or registration section at the beginning of the activity because data collection is still handwritten. The purpose of making this application is to make it easier for the Information Technology faculty to carry out existing activities so that it can shorten time and reduce errors that occur at the beginning of registration.